2019
DOI: 10.3390/cells8121655
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxin 16’s Newly Deciphered Roles in Autophagy

Abstract: Syntaxin 16, a Qa-SNARE (soluble N-ethylmaleimide-sensitive factor activating protein receptor), is involved in a number of membrane-trafficking activities, particularly transport processes at the trans-Golgi network (TGN). Recent works have now implicated syntaxin 16 in the autophagy process. In fact, syntaxin 16 appears to have dual roles, firstly in facilitating the transport of ATG9a-containing vesicles to growing autophagosomes, and secondly in autolysosome formation. The former involves a putative SNARE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…Our results indicated that alcohol upregulates the expression of VAMP3, VAMP5 and VAMP7 and synatxin16 in hepatocytes and increased levels of these SNAREs were also found in ALD patients. VAMP3, VAMP7 and syntaxin16 were shown to mediate fusion between MVBs with autophagosomes and autolysosome formation (Miller and Shindell, 1998;Tang, 2019), and we recently described a link between miR-155 and lysosome dysfunction and exosome production (Babuta et al, 2019). VAMP7 was also demonstrated to participate in the fusion between MVBs with the plasma membrane to release exosomes (Fader et al, 2009).…”
Section: Mirna-192 Regulates the Exosome Secretion Via Targeting Rabs...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicated that alcohol upregulates the expression of VAMP3, VAMP5 and VAMP7 and synatxin16 in hepatocytes and increased levels of these SNAREs were also found in ALD patients. VAMP3, VAMP7 and syntaxin16 were shown to mediate fusion between MVBs with autophagosomes and autolysosome formation (Miller and Shindell, 1998;Tang, 2019), and we recently described a link between miR-155 and lysosome dysfunction and exosome production (Babuta et al, 2019). VAMP7 was also demonstrated to participate in the fusion between MVBs with the plasma membrane to release exosomes (Fader et al, 2009).…”
Section: Mirna-192 Regulates the Exosome Secretion Via Targeting Rabs...mentioning
confidence: 99%
“…The vSNARE protein, VAMP7 was demonstrated to mediate the fusion of secretory lysosomes with the plasma membrane and to regulate of EVs release (Fader et al, 2009). Syntaxins belong to t-SNAREs proteins and play an important role in membrane trafficking and autophagy (Tang, 2019;Mori et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence demonstrates that Syntaxin (Stx)5, Stx17, and Stx16 are involved in the autophagy pathway (Tang, 2019). Stx17 is a SNARE protein mainly localized in the ER and partly in the ERGIC (Muppirala et al, 2011) and is essential for maintaining the architecture of ERGIC and the Golgi (Muppirala et al, 2011), and it contributes to the autophagy pathway at several stages from initiation to maturation (Gu et al, 2019).…”
Section: Soluble N-ethylmaleimide-sensitive-factor-attachment Proteinmentioning
confidence: 99%
“…In addition, Stx17 interacts with mAtg8s via the LIR motif and inserts into the autophagosomal membrane (Kumar et al, 2018;Shen et al, 2020). Stx16 is localized in the late Golgi compartments, receives retrograde transport from the endosomes (Xu et al, 2002), and is involved in autophagy by facilitating the transport of ATG9a-containing vesicles to growing autophagosomes (Tang, 2019). Moreover, stx16 is recruited by Atg8/LC3/GABARAP family proteins to autophagosomes and endolysosomes (Tang, 2019).…”
Section: Soluble N-ethylmaleimide-sensitive-factor-attachment Proteinmentioning
confidence: 99%
See 1 more Smart Citation